2022
DOI: 10.3389/fevo.2022.1075914
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of habitat quality and analysis of influencing factors in the Yellow River Delta Wetland from 1986 to 2020

Abstract: The assessment of habitat quality plays an important role in the effective conservation of wetland biodiversity. The Yellow River Delta Wetland is located in the intertwining zone of sea, terrestrial, and river ecosystems, increasing human activities and climate change posed a great threat to wetland biodiversity. This study first analyzed the spatial and temporal evolution characteristics of habitat quality in the Yellow River Delta Wetland under the evolution of the shoreline after runoff-sediment variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Zhang et al found that the habitat quality in 2020 increased compared to that in 2011, which is mainly due to the background of the major strategy of ecological protection and high-quality development of the Yellow River basin and the continuous ecological replenishment work since 2008. More policies and management measures have been implemented to strengthen the protection of the Yellow River Delta Wetland [44]. This aligns with the findings of a previous study, indicating an increase in…”
Section: Spatial Differentiation Of Land Use Changesupporting
confidence: 90%
“…Zhang et al found that the habitat quality in 2020 increased compared to that in 2011, which is mainly due to the background of the major strategy of ecological protection and high-quality development of the Yellow River basin and the continuous ecological replenishment work since 2008. More policies and management measures have been implemented to strengthen the protection of the Yellow River Delta Wetland [44]. This aligns with the findings of a previous study, indicating an increase in…”
Section: Spatial Differentiation Of Land Use Changesupporting
confidence: 90%
“…The digital elevation model (DEM), slope (SLO), and terrain roughness index (TRI) [42] are important geographical parameters to measure the terrain and landform of the study area. The human footprint index (FHI) [62] and gross domestic product (GDP) [38] are important human factors used to reflect the intensity of human activities. FHI reflects 8 variables of different aspects of human pressure, such as the built environment, population density, night light, cropland, pasture, road, railway, and navigable waterway.…”
Section: ) Spearman Rank Correlation Analysis Methodsmentioning
confidence: 99%
“…Physicochemical variables measured in this study were temperature, dissolved oxygen, conductivity, pH, secchi disk depth a.m., and p.m., total dissolved substance, salinity, nitrite (NO 2 ), nitrate (NO 3 ), soluble reactive phosphorous, total ammonia (NH 4 + NH 3 ), total phosphorus (TP), total nitrogen (TN), and chlorophyll a (Chl-a). These variables were monitored because they de ne the status and quality of the water and phosphorous can be directly harmful to sh in concentrations beyond the normal ranges (Zhang et al, 2022;Dar et al, 2021;Lopes, 2021;Holmes & Taylor, 2015). Temperature affects the speed of chemical reactions, the rate of photosynthesis, the metabolic rate of aquatic organisms, as well as how pollutants, parasites, and other pathogens interact with aquatic residents.…”
Section: Measurement Of Physicochemical Variablesmentioning
confidence: 99%